The life of Roman republicanism - Connolly, Joy, 1970- (Princeton University Press, 2015)
Joy Connolly argues that Cicero, Sallust, and Horace inspire fresh thinking about central concerns of contemporary political thought and action. These include the role of conflict in the political community, especially as it emerges from class differences; the necessity of recognition for an equal and just society; the corporeal and passionate aspects of civic experience; citizens' interdependence on one another for senses of selfhood; and the uses and dangers of self-sovereignty and fantasy. Putting classicists and political theorists in dialogue, the book also addresses a range of modern thinkers, including Kant, Hannah Arendt, Stanley Cavell, and Philip Pettit. Together, Connolly's readings construct a new civic ethos of advocacy, self-criticism, embodied awareness, imagination, and irony.--Provided by publisher.